(3EVGAI GdQGehS hEVGaI GdfGehS Ydi EVGAI GdbGehSs - (3eMeO Hf GdWjH eMeO Hf eMeO Hf eMeO GdTQbj GdaGSj GdeGdcj, CHh YHO Gddg , J (B1170 (3g`s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3TLf ef GdbGehS GdeMjW , QTMI ef BKGQ BjGJg , hGdbGHhS GdhSjW deMg ef CfhGQ BjGJ , adg GdMeO CSGS eLO GdOjf CeG HYO , aEf Chdi eG jZTi Hg GdeYfi HGdYdhe GdegeI GdZhU ai bGehS GddZGJ s
(3BNQgG (B:s
(3ef eGOI LjH , bhdg (B: (3bhdg hMeRI GdLjGH EdN CHfGA GdLjGH LeGYI ef GdeMOKjf , hajge TjhN GdYjGV hGHf GdYQHi GdbGVi hZjQge ef GdCYdGe Cgedge ced GdLRA GdChd HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdedcjI (B- (3GdQHGW (B(1/544) s
Keywords: (3GddZIs